2015
DOI: 10.1177/0739986314565974
|View full text |Cite
|
Sign up to set email alerts
|

Mexicanness and Social Order in Digital Spaces

Abstract: This article explores how younger members of a multigenerational social network of transnational Mexicans of ranchero background construct their ethnic identity both in offline and online contexts. By using traditional ethnography and discourse-centered online ethnography (DCOE), this study found that members of this network use four emic criteria (language, color, transnationality, and display of culture) to construct their ethnic identity as Mexican. In the online context, members use these criteria to chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 16 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…The current study develops from a long-term ethnographic project focused on this same transnational social network of Mexican families but which examines the role of language ideologies and language practices in the construction of their ethnic identities (cf. Christiansen, 2015a;2015b, 2016a2016b). For the current study, a social network approach (Milroy, 2002) is adopted to generate a contextualized analysis of discourse practices in order to explore how participants specifically use their languages along with other online resources to communicate across borders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study develops from a long-term ethnographic project focused on this same transnational social network of Mexican families but which examines the role of language ideologies and language practices in the construction of their ethnic identities (cf. Christiansen, 2015a;2015b, 2016a2016b). For the current study, a social network approach (Milroy, 2002) is adopted to generate a contextualized analysis of discourse practices in order to explore how participants specifically use their languages along with other online resources to communicate across borders.…”
Section: Methodsmentioning
confidence: 99%
“…Vieira, 2011Vieira, , 2016. While scholars continue to study how transnationals communicate in new digital spaces, especially their language choice and literacy practices (Berry, Hawisher, & Selfe, 2012;Burrell & Anderson, 2008;Christiansen, 2015b;Lam & Rosario-Ramos, 2009;Louie, 2004;Madianou & Miller, 2012), we have not focused much on how digital communication contributes to their construction of transnational social spaces. Transnational social spaces are crucial sites where transnational individuals "cultivate, support, and nurture their transcultural activities and identities" (Yi, 2009, p. 115), and they are extremely important for social and academic development (Lam, 2009;Lam & Warriner, 2012).…”
mentioning
confidence: 99%
“…Despite the insight this case study brings to understudied intersections, there are some limitations. For individuals within transnational families, there are different levels of engagement in transnationality (Christiansen 2015). Given the secondary nature of the data, we were unable to determine the level of transnationality José-Luis incorporated into his own identity.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Transnationality often emphasizes the fluidity of relationships between family members in two or more countries (Christiansen 2015). However, examination of the experiences of transnational fathers is limited by largely comparative research which views immigrant families through a lens of cultural and developmental deficits (Strier and Roer-Strier 2010).…”
Section: Transnational Familiesmentioning
confidence: 99%
“…The author interprets group members' alternation between embracing and distancing themselves from ranchero culture as a performance that is "reminiscent of their collective past but fitted to contemporary U.S. Mexican culture" (Christiansen 2015a, p. 699). In another study of the same online ranchero community, Christiansen (2015b) found that individuals use their perceived degree of "centrality" to ranchero culture, social networks, and the Spanish language to position themselves as more or less Mexican in an online environment.…”
Section: Introductionmentioning
confidence: 99%